Effects of a 9-month neuromuscular training program on isometric & dynamic force-time characteristics & vaulting take-off velocity in young gymnasts - Moeskops, S.; Read, P.; Haff, G.; Oliver, J.; Myer, G.; Cronin, J.; Lloyd, R. (The Journal of Strength and Conditioning Research, 2021)
Previous research exploring the effectiveness of neuromuscular training (NMT) programs in young female gymnasts [1,2] have primarily implemented short-term interventions and failed to examine the training benefits on gymnastics performance. Purpose: To examine the effects of a 9-month NMT intervention on isometric and dynamic force-time characteristics during strength and power tests and vertical take-off velocity during gymnastics vaulting. Methods: Forty-three pre-pubertal female gymnasts were sub-divided into gymnastics + NMT (GYM + NMT; n = 16), gymnastics only (GYM, n = 15) groups and a maturity-matched control (CON; n = 12). Biological maturation was estimated using percentage of predicted adult height (%PAH) [3]. The GYM + NMT group followed a 9-month NMT program, consisting of 2 × 1-hr sessions/week, while the GYM and CON groups did not receive the additional training stimulus. Force-time characteristics during the isometric mid-thigh pull (IMTP), countermovement jump (CMJ), and drop jump (DJ) tests were measured at baseline (T1) and thereafter on a 3-monthly basis (T2, T3 and T4). Vertical take-off velocity during a straight jump vault was calculated using 2D video analysis. A 3 × 4 (group × time) repeated measures ANOVA with a Bonferroni post-hoc analysis was used to identify any significant between-group differences (p < 0.05), and Hedges' g to calculate effect sizes [4]. Results: Data indicated moderate significant increases in IMTP absolute peak force (PFabs) from baseline to each subsequent testing session and relative peak force (T1-T3 and T1-T4) in the GYM + NMT, and a small significant increase in PFabs from T1-T4 in the GYM group (Table 1). CMJ data showed jump height (JH) and braking impulse (Impulsebrake) significantly increased from T1-T3 in the GYM + NMT group, while propulsive impulse (Impulseprop) significantly increased from baseline to each subsequent testing session. Impulseprop was the only measure that significantly increased in the GYM group (T1-T4). DJ data revealed significant improvements in JH and reactive strength index (RSI) from T1-T3 and T1-T4 in the GYM + NMT, with no significant changes in the GYM group. Significant increases in vaulting vertical take-off velocity were only identified in the GYM + NMT (T1-T4). CON group showed no significant changes, other than a significant increase in DJ contact time (T1-T4). Conclusions: The additional NMT stimulus significantly improved vaulting vertical take-off velocity, maximal isometric force producing capabilities, and slow and fast-stretch shortening cycle function in the GYM + NMT cohort; however, these changes were not evident for GYM or CON. Practical Applications: Positive changes in isometric and dynamic kinetic variables can be achieved in prepubertal female gymnasts following 3 months of NMT and appear to be beyond those obtained from gymnastics alone. Practitioners should realise that the beneficial effects from NMT may take longer to transfer to vaulting performance.